ANXIETIES RELATED TO CAREER CHOICE AND THE NECESSITY OF THEIR STUDY - Sadullayeva Sevara Maksudbekovna (PEDAGOGS, 2025)
Abstract: This article provides an in-depth analysis of the psychological anxieties that arise during the process of choosing and pursuing a career, their types, causes, and age-related characteristics. In particular, it highlights the internal conflicts that occur during adolescence and early adulthood due to career uncertainty, lack of self-confidence, social pressure, and expectations. The article emphasizes that such anxieties can negatively affect not only individual development but also socio-economic balance.